Genomic collinearity and the genetic architecture of floral differences between the homoploid hybrid species Iris nelsonii and one of its progenitors, Iris hexagona - Taylor, S J (Nature Publishing Group, 2013)
Hybrid speciation represents a relatively rapid form of diversification. Early models of homoploid hybrid speciation suggested that reproductive isolation between the hybrid species and progenitors primarily resulted from karyotypic differences between the species. However, genic incompatibilities and ecological divergence may also be responsible for isolation. Iris nelsonii is an example of a homoploid hybrid species that is likely isolated from its progenitors primarily by strong prezygotic isolation, including habitat divergence, floral isolation and post-pollination prezygotic barriers. Here, we used linkage mapping and quantitative trait locus (QTL) mapping approaches to investigate genomic collinearity and the genetic architecture of floral differences between I. nelsonii and one of its progenitor species I. hexagona. The linkage map produced from this cross is highly collinear with another linkage map produced between I. fulva and I. brevicaulis (the two other species shown to have contributed to the genomic makeup of I. nelsonii), suggesting that karyotypic differences do not contribute substantially to isolation in this homoploid hybrid species. Similar to other studies of the genetic architecture of floral characteristics, at least one QTL was found that explained >20% variance in each color trait, while minor QTLs were detected for each morphological trait. These QTLs will serve as hypotheses for regions under selection by pollinators.